2008
DOI: 10.1103/physrevb.77.125406
|View full text |Cite
|
Sign up to set email alerts
|

Double-segregation effect inAgxPd1xRu(0001)thin film nanostructures

Abstract: We study the structural properties of ultrathin Ag x Pd 1−x films on top of a Ru͑0001͒ substrate. Effective interatomic interactions, obtained from first-principles calculations, have been used in Monte Carlo simulations to derive the distribution of the alloy components in a four-monolayer ͑4-ML͒ Ag-Pd film. Though Ag-Pd alloys show complete solubility in the bulk, the thin film geometry leads to a pronounced segregation between Ag and Pd atoms with a strong preference of Ag atoms toward the surface and Pd at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…More specifically considering core-level shifts, there are several experiments [6,80,50], while theoretical works include results for bulk [16][17][18], surface [23] and thin films [25,91]. A difference between older and newer experimental values was attributed to measurements performed on surface alloys rather than bulk in the older study [50].…”
Section: Average Global Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically considering core-level shifts, there are several experiments [6,80,50], while theoretical works include results for bulk [16][17][18], surface [23] and thin films [25,91]. A difference between older and newer experimental values was attributed to measurements performed on surface alloys rather than bulk in the older study [50].…”
Section: Average Global Environmentmentioning
confidence: 99%
“…Apart from interface qualities, there is a possibility of considering CLSs as a way to monitor special interface states. Also, one interesting option is to consider Monte Carlo methods, see for example the computation of the double segregation effect in AgPd alloy on Ru(0001) [91], in order to determine candidate structures for CLS calculations. In future work, it would be of interest to study the effect of the local environments in more detail, for instance using supercell techniques.…”
Section: Core-level Shift In Embedded Thin Filmsmentioning
confidence: 99%
“…For nanoparticles and extended surfaces, it has been demonstrated that reactions may drive restructuring and segregation. In the case of PdAg alloys, silver segregation to the surface under ultra high vacuum (UHV) conditions has been observed experimentally, 11,12 and predicted from calculations. [13][14][15][16][17][18][19] The segregation originates from the lower surface energy of Ag as compared to Pd 15,17,20,21 and from the reduction of stress owing to the slightly larger Ag atoms.…”
mentioning
confidence: 98%
“…Core-level photoemission has also been used to probe the substrate atoms at group-10/early-transitionmetal interfaces [8,[19][20][21][22][23], but except for core-level measurements of W(111) by Tao et al [20], none of this work has been particularly systematic. This is unfortunate because the substrate shifts provide a view of the interface that is complementary to the adlayer shifts.…”
Section: Introductionmentioning
confidence: 99%